Anti-money laundering and counter financing of terrorism regulation of banking institution in Malaysia - Mohd. Yasin , Norhashimah (INSI Publications, 2012)
The Anti-Money Laundering and Anti-Terrorism Financing Act 2001 (AMLATFA) is the sole legislation dealing with this matter in Malaysia. Part 4 of this Act is the basic regulation for ‘reporting institutions’, including all types of bank. As Part 4 is only general, the Malaysian Central Bank as the ‘Competent Authority’ has issued detailed Guidelines. All ‘reporting institutions, banks included, must follow the Standard Guidelines (UPW/GP1). There are ten Sectoral Guidelines UPW/GP1[1] is for banks. Failure to follow the Act and the associated Guidelines could result in severe legal consequences.